Utilizing Zoos Victoria's Connect‐Understand‐Act model to enable social and biological gains in northern Kenya. Issue 1 (19th April 2016) - Squires, B.; Lowry, R.; Banks, C.
Abstract : As human populations grow, wildlife across the globe is increasingly threatened. As a zoo‐based conservation organization, Zoos Victoria (ZV) in south‐east Australia is dedicated to fighting wildlife extinction locally and globally. Our international partnerships work with local communities, governments and non‐governmental organizations. The focus of the ZV conservation programmes is on alleviating threats to wildlife while addressing the needs of the community. The shared vision of a partnership with the Melako Community Conservancy (MCC) in northern Kenya is to foster sustainable development that allows communities to live in balance with wildlife. In 2011, an opportunity arose to trial ZV's Connect‐Understand‐Act (CUA) model for influencing visitor behaviour change, and this led to the first practical application of this model in Kenya. The model utilizes best‐practice conservation, education and social science to shape wildlife‐friendly values and behaviours. The impact of this model is now being trialled in situ through a conservation‐based sports programme called 'Kicking Goals for Wildlife'. After conducting a conservation‐needs assessment in 2010, the community identified human–wildlife conflict as an issue negatively impacting species such as the Beisa oryx Oryx gazella beisa and Grevy's zebra Equus grevyi . The Kicking Goals for Wildlife programme is targeted at morans (initiated youth ranging from 15 to 30 years of age, and also referred to as warriors), filling their 'idle time' with football as an alternative to harming wildlife or engaging in intertribal conflict. The outcomes of the programme will be measured through changes in warrior attitude, knowledge, behavioural efficacy, reduction in biological threat and social change. Preliminary feedback is showing positive progress across all aspects. An additional measure, in an effort to assess the programme's impact on target species, was distance sampling to monitor the changes in flight distance. This paper outlines the theoretical framework underpinning the model, using the Kicking Goals for Wildlife programme in the MCC as a case study for what is involved in planning, designing and implementing a conservation‐education programme in the field.